Identifying Features of Resilience to Childhood Maltreatment in Resting-State Connectivity Data From Adults With and Without a History of Mood Disorder - Mindy Westlund Schreiner; Leah R. Thomas; Ha D.H. Le; Myah Pazdera; Daniel A. Feldman; Brian Farstead; Katie L. Bessette; Robert C. Welsh; Sheila E. Crowell; Erin A. Kaufman; Heide Klumpp; Scott A. Langenecker (Biological Psychiatry Global Open Science)
Background: Childhood maltreatment (CM) is associated with negative mental health outcomes. Many studies conceptualize resilience as experiencing CM without developing psychopathology (primary resilience). However, some people may develop subsequent psychopathology but recover and demonstrate higher global functioning (secondary resilience). This study investigated the role of salience and emotion network (SEN) (including the amygdala, subgenual anterior cingulate cortex, and anterior insula) and cognitive control network (CCN) (including the dorsolateral prefrontal cortex, inferior parietal lobule, and thalamus) connectivity in primary and secondary resilience. Methods: We examined resting-state functional connectivity in 108 nonclinical control participants and 154 individuals with any mood disorder (AMD). We measured functioning and CM using the Global Assessment of Functioning (GAF) scale and the Childhood Trauma Questionnaire (CTQ), respectively. For primary resilience, we conducted whole-brain analyses of SEN and CCN regions to test for group × CTQ interactions. For secondary resilience, within-AMD group analyses tested for CTQ × GAF interactions. Results: Group × CTQ interactions revealed that control participants with higher levels of CM showed greater within-SEN and within-CCN connectivity than participants in the AMD group. In the AMD group, participants with higher levels of CM and functioning (secondary resilience) showed greater within-CCN connectivity while participants with higher levels of CM and lower functioning showed greater within-SEN connectivity. Conclusions: Greater SEN connectivity appears to play a key role in primary resilience, as observed in the control group, but only within the context of greater CCN connectivity. Future work should explore which cognitive control features are most beneficial and whether targeted interventions help foster resilience to recurrent psychopathology.